Blood Pressure Seasonality in Hemodialysis Patients from Five European Cities of Different Latitudes - Flore Duranton; Alfonso Palma; Bernd Stegmayr; Michel Wauthier; Armando Torres; Àngel Argilés (Kidney & Blood Pressure Research, 2018)
Background/Aims: Climate influences the regulation of blood pressure (BP). Our objective was to precisely estimate BP seasonality in hemodialysis (HD) patients from five European cities with marked climate differences. Methods: Stable prevalent HD patients from 5 European facilities (Santa Cruz de Tenerife (Spain), Seville (Spain), Montpellier (France), Ottignies (Belgium), Umea (Sweden)) present over the years 1995-1999 were included in this historical longitudinal observational study. Individual monthly averages of pre-dialysis BP level were computed from all facility BP measurements (> 90 000 observations). The association between BP level and location, seasons and meteorological measurements was analyzed by mixed models. Results: 261 patients were included and followed-up for a median duration of 2 years (6903 monthly observations). Pre-dialysis SBP and DBP were minimal in summer (July) and maximal in winter (November and December), and mean changes were respectively 4.2 [3.0; 5.4] and 2.0 [1.3; 2.7] mmHg. Seasonality was confirmed in 4 locations (Pseason≤0.001 for SBP and DBP), but not in Umea (both Pseason> 0.05). Seasonal changes in DBP were larger in southern locations (Pinteraction=0.02). BP level was associated with climate parameters: in a positive manner with humidity or rainfall, and inversely with sunshine duration or temperature. The effects of temperature and rainfall on DBP varied with latitude (Pinteraction< 0.02) and were greater in southern locations. Conclusion: BP varies with seasons and climate in different European areas and seasonality can be more important in southern locations. These changes in BP deserve attention as they may be responsible for a significant increase in cardiovascular risk which may be preventable.